(untitled) (Journal Of Educational and Psychological Researches, 2017)
The Islamic religion approach Rabbani urges and seeks to bring happiness to people, as Allah says: ((We sent thee not all people glad tidings and a warner, but most people do not know)) Spa: State 28 Islam looks at the concept of educational values ​​through positive behavior derived emerging through formal and informal education. The Islamic approach works on the basis of a systematic and clear rule in the form of an integrated system includes multiple areas. As the lead actor role as the desired position. Although responsible behavior which seeks to establish the rules of Islamic approach comes through enlightened awareness, which includes cognitive aspect is the basis for building an educational ad valorem system. It is awareness of this premise is the first level of the correct value trends. Values ​​and is an important part of the historical and cultural heritage of any society, and in order to remain united and coherent, it must be based on rules and principles fixed based on the systems of values ​​reflect the nature of society and its properties is based; this is a question of values ​​of interlocking and complex issues that are still disputed